Sir Nigel - Doyle, Arthur Conan (Saga Egmont, 2022)
Set in the middle of the 14th century, Sir Nigel is a swashbuckling story of the eponymous hero as he seeks his fortune & the hand of his lady-love in England & France in the early part of the Hundred Years War. It is full of high romance & chivalry, battles & brutality, humor & sheer rumbustiousness as the impoverished Nigel Loring & his attendant Aylward seek their fortunes. Edward III, the Black Prince, Sir John Chandos — one of the original Knights of the Garter — all make their appearances in one of the favorite books from the pen of the creator of Sherlock Holmes.